Mathematical modelling of pollution dynamics of circumterrestrial orbits - Пилькевич, Игорь Анатольевич (Eastern-European Journal of Enterprise Technologies, 2010)
The method of practical calculation of speed and elements concentration in each point of space during the set moment of time based on the decision of the equations mechanics, the coordinates generated in specially chosen system is developed. By consecutive use of specially proved theorems possibility and a construction technique of special systems of co-ordinates is proved.